Developing collaborative system for open source software development community. - Lakulu, Modi; Abdullah, Rusli; Samsudin, Khairulanuar (2012)
The OSS community plays a very important role in contributing to and sharing of the knowledge that can ensure the sustainability of OSS. At this crucial juncture, this paper discusses the software development that was aimed to strengthen the OSS community through a series of collaborative tools, namely forum, chat and email. The development of the system used the prototype approach and a follow-up survey on system usability was conducted involving OSS developers, which are based in Selangor, Perak, Putrajaya, and Kuala Lumpur. Findings from the survey showed that an overwhelming majority of the respondents agreed that the design aspects of the user interface and the functionality of the system had been addressed appropriately. These important findings reinforces that the current design of such a system could be developed into a full fledge collaborative system that would help the sharing of knowledge among the Community-of-Practice to embark into software development activities.